Perbandingan Metode Forward Chaining dan backward Chaining Pada Aplikasi Sistem Pakar Identifikasi Gaya Belajar - Retno Retno Apriliyani (E-Jurnal Universitas Samudra, 2022)
Each individual has a different learning style, so they must know their learning style to speed up and facilitate the learning process. Identification of learning styles in general is still done by consulting directly with psychologists or filling out the questionnaire sheet provided, so the process of drawing conclusions also takes a long time because it still uses manual calculations. Thus, an expert system for identifying learning styles is needed to streamline time and make it easier for each individual to consult about their learning style tendencies. The learning style identification expert system was built using the forward chaining and backward chaining methods as well as the research method in the form of an experimental method that aims to compare the two expert system methods based on several aspects including accuracy of conclusions, ease of use, suitability and satisfaction of conclusion results, efficiency of the identification process and its usefulness to psychology or BK teacher in identifying learning styles. The results showed that the forward chaining method was superior to the backward chaining method, including in terms of accuracy of conclusions, 95% ease of use, 90% compatibility and satisfaction with conclusions, and 95% usefulness for psychology or counseling teacher. While the backward chaining method excels in the aspect of process efficiency only with a percentage of 87,5%.